The use of magnetic resonance imaging to evaluate the accuracy of a handheld ultrasound machine in localizing the sciatic nerve in the popliteal fossa. Issue 5 (1st September 2004) - Sites, Brian D.; Gallagher, John D.; Tomek, Ivan; Cheung, Yvonne; Beach, Michael L.
Abstract : Background and objective: Ultrasound has become an increasingly popular modality in facilitating the performance of peripheral nerve blocks. There is a paucity of data describing techniques of ultrasound-guided sciatic nerve blocks. By using magnetic resonance imaging (MRI) as a gold standard, the objective of this study was to describe the ability of a handheld ultrasound machine to accurately locate the sciatic nerve. Methods: Ten patients were prospectively enrolled and placed in the prone position. By using a 4- to 7-MHz ultrasound transducer, the sciatic nerve was visualized in short axis between 5 to 10 cm above the popliteal crease. The distance from the skin to the nerve was measured by ultrasound, and a MRI lucent marker was placed at this site. This process was repeated in one additional location. The patient was then placed supine in the MRI scanner and short-axis T1-weighted images were obtained. On the MRI image, we recreated the 2 lines extending down from the markers using the distances previously measured by ultrasound. The point of intersection of these 2 lines represents the ultrasound-determined location of the sciatic nerve, which was then compared with the midpoint of the nerve complex on MRI. Results: The sciatic nerve was easily visualized by ultrasound in all 10 patients. MRI showed the division of the sciatic nerve in 9 out of 10 patients. Ultrasound was able to confirm this division in 7 patients. The mean distance between the MRI and ultrasound midpoint location of the sciatic nerve was 2.9 ± 1.3 mm. Conclusions: The data presented here suggest that the specific ultrasound machine evaluated in this study can accurately localize the sciatic nerve in the popliteal fossa.